PENENTUAN WAKTU PENYALAAN LAMPU LALU LINTAS YANG OPTIMAL : KASUS PERSIMPANGAN BUAH BATU LINGKAR SELATAN - Hayun, Anggara; Sundari, Sundari (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
Traffic Light Signals play important roles to control intersection. Now the biggest problem of traffic light signals are timing parameter and phasing are not suitable with volume and characteristic of arrival and caused overload queue in node or internodes. Webster already developed queue models for optimum determining traffic light time, so waiting time can be minimized. This research used Websterâs queue modeling. The results shows that with changing phase movement, waiting time decrease until 25,59 %.